Ethnobotany of Weeds in Kanchanpur District, Far-Western Nepal - Bhatt, Man Dev; Adhikari, Yagya Prasad; Kunwar, Ripu (Ethnobotany Research and Applications, 2021)
Background: Far-Western Terai Region of Nepal is a large source of floral diversity. Most of the plants are medicinal and available as wild or weeds. Weeds are unwanted plants and competing with crop plants for common resources (water, mineral nutrients, space, and light) and reduce the yield of wanted plants. However, the weeds and their medicinal properties were scarcely documented. The aim of the present study was to explore the diversity of commonly used weeds of Kanchanpur district, to be precise on cataloguing the indigenous knowledge how local weeds are managed and utilized by local people. Methods: The study district is border to India at southwestern part of the country. The information of weeds and their medicinal uses was collected by using semi-structured questionnaires in which participatory rural appraisal (PRA) and rapid rural appraisal (RRA) tools were used. The quantitative data were analyzed by use value (UV), informant consensus factor (ICF), Fidelity Level (FL), and Relative Frequency of Citation (RFC). Results: A total of 108 weed species were recorded under 44 families as medicinal to treat different ailments. Among them, 79 species were dicotyledons, 25 monocotyledons (19 grasses and 6 sedges species) and 4 pteridophytes. The composition of species to their respective families showed the highest (12%) occurrence by families Poaceae and Asteraceae with first rank and the lowest (1%) occurrence by families Alismataceae and Typhaceae with sixth rank category. Weed species were being used as similar to other plant species used for ethnobotany, however the use as ethnomedicinal was remarkable. The medicinal use of weeds with the highest Informant Consensus Factor (ICF) (0.75) was for fever and in palpitation of heart and the lowest ICF (0.45) for paralysis and arthritis. The Use Value (UV) and Relative Frequency of Citation (RFC) were used to demonstrate that which weeds could be further used for pharmacological study and advancement of drug discovery. Conclusions: The finding proved the significance of weeds as medicine so there is a dire need to create awareness among the people for conservation and sustainable use of these weeds. Although weeds are undesirable plants, but they have high medicinal values, thus their controlled cultivation might be necessary as extensive cultivation may have bad impact on normal crops. The information of weed species and their use to treat various ailments must be explored, preserved, documented, and transferred from generation to generation. Keywords: Ethnomedicine, Indigenous knowledge, Kanchanpur, Nepal, Weeds.